2009
DOI: 10.1007/s10840-009-9365-z
|View full text |Cite
|
Sign up to set email alerts
|

Segmental pulmonary vein isolation in atrial fibrillation: new insights from the high density mesh mapper technique in an electrophysiologically guided approach

Abstract: In this first prospective study of PV isolation using the HDMM, our findings suggest, that this method is safe and yields good primary success rates and favourable clinical outcome at 6 month. The new technology based on high resolution recordings, offers beside good anatomical orientation a direct electrophysiological control for monitoring of bidirectional conduction block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Our group described, that the majority of the PVs could be examined despite the relatively stiff mapping tool 4. The mesh offers beside excellent electrophysiological control a very good 3d orientation because of the basket configuration, which allows an easy anatomical understanding, even at the complex LA-PV junction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group described, that the majority of the PVs could be examined despite the relatively stiff mapping tool 4. The mesh offers beside excellent electrophysiological control a very good 3d orientation because of the basket configuration, which allows an easy anatomical understanding, even at the complex LA-PV junction.…”
Section: Discussionmentioning
confidence: 99%
“…The HDMM electrode (Figure 1) and the ablation procedure had been described by our group 4 and Neumann et al 9. Under fluoroscopy, the transseptal puncture (TSP) was done twice, first for the HDMM, the high-density mapping catheter, and second for the RF ablation catheter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies reported that the rate of exit conduction after the entrance block of the PV‐LA junction in patients undergoing segmental PV isolation can be as high as 42% 9–11 . However, some pitfalls should be noted in those studies.…”
Section: Introductionmentioning
confidence: 99%